In situ construction of ZnFe2O4 nanospheres on CoO nanosheets for durable photodegradation of organics: kinetics and mechanistic insights. (25th August 2022) - Okla, Mohammad K.; Subhiksha, V.; Akshhayya, C.; Al-amri, Saud S.; Alaraidh, Ibrahim A.; Al-ghamdi, Abdullah A.; Soufan, Walid; Abdel-Maksoud, Mostafa A.; Aufy, Mohammed; Studenik, Christian R.; Khan, S. Sudheer
Abstract : The development of a low-cost, efficient and sustainable technology is considered to be of paramount for the efficient degradation of toxic pollutants. Abstract : The development of low-cost, efficient and sustainable technology is considered to be of paramount for the efficient degradation of toxic pollutants. The research in this report constructs an S-scheme heterojunction CoO/ZnFe2 O4 nanocomposite (NCs) with outstanding photocatalytic performance on methylene blue (MB) dye degradation under visible light illumination. Several techniques were used for nanoparticles (NPs) and NCs to determine their morphological, structural, and optical properties. The CoO/ZnFe2 O4 NCs (88.5%) exhibited excellent photocatalytic activity compared to the pristine CoO (66.8%) and ZnFe2 O4 (64.3%). The total organic carbon (TOC) analysis confirmed that the MB dye was completely mineralised by the as-prepared NCs. From the results of the GC-MS/MS analysis, a possible intermediate formation and degradation pathway was identified. The h + and ˙OH are the free radicals which primarily dominate the photocatalytic process. A recyclability study performed on the CoO/ZnFe2 O4 NCs revealed that it was an extremely stable catalyst, even after six cycles, without substantial decreases in its degradation activity. The intermediate toxicity was predicted using ECOSAR software and the results confirmed the non-toxicity of the end product formed during the degradation of the MB dye.